The pancreatic tumor microenvironment of treatment-naïve patients causes a functional shift in γδ T cells, impairing their anti-tumoral defense - Elena Lo Presti; Francesca Cupaioli; Daniela Scimeca; Elettra Unti; Vincenzo Di Martino; Rossella Daidone; Michele Amata; Nunzia Scibetta; Erinn Soucie; Serena Meraviglia; Juan Iovanna; Nelson Dusetti; et al. (OncoImmunology)
Pancreatic ductal adenocarcinoma (PDAC) presents a unique challenge for researchers due to its late diagnosis caused by vague symptoms and lack of early detection markers. Additionally, PDAC is characterized by an immunosuppressive microenvironment (TME), making it a difficult tumor to treat. While γδ T cells have shown potential for anti-tumor activity, conflicting studies exist regarding their effectiveness in pancreatic cancer. This study aims to explore the hypothesis that the PDAC TME hinders the anti-tumor capabilities of γδ T cells through blockade of cytotoxic functions. For this reason, we chose to enroll PDAC treatment-naive patients to avoid the possibility of therapy modifying the TME. By flow cytometry, our research findings indicate that the presence of γδ T cells among CD45+ cells in tumor tissue is lower compared to CD66+ cells, but higher than in blood. Circulating Vδ1 T cells exhibit a terminal effector memory phenotype (TEMRA) more than Vδ2 T cells. Interestingly, Vδ1 and Vδ2 T cells appear to be more prevalent at different stages of tumor development. In our in vitro culture using conditioned medium derived from Patient-derived organoids ;(PDOs), we observed a shift in expression markers in γδ T cells of healthy individuals toward an activation and exhaustion phenotype, as confirmed by scRNA-seq analysis extracted from a public database. A deeper understanding of γδ T cells in PDAC could be valuable for developing novel therapies aimed at mitigating the impact of the pancreatic tumor microenvironment on this cell population.